Penyelesaian Sengketa Ekspresi Budaya Tradisional (EBT) Dalam Bingkai Copying-Plagiarism: Resolution of Traditional Cultural Expression (TCE) Disputes in the Context of Copying and Plagiarism - Elkristi Ferdinan Manuel (Fakultas Hukum Universitas Tompotika Luwuk Banggai, 2025)
The purpose of this study is to analyse how the settlement of Intellectual Property Rights (IPR) disputes can distinguish between Copyright issues and Traditional Cultural Expressions (TCE), as well as to provide a contextual explanation of the elements of copying and plagiarism in conflicts involving local culture. The method employed is juridical-normative, incorporating a legislative, and conceptual approach. The results of the study show that the modern IPR system based on individualistic principles has not been able to accommodate the collective nature and spirituality of NRE. Reform of the community-based legal system, strengthening the doctrine of the idea-expression dichotomy, and documentation mechanisms based on community participation are needed. Disputes involving copying and plagiarism should be understood not only as a violation of the law, but also as a matter of ethics and cultural justice.